Additive asymmetric quantum codes - Ezerman, Martianus Frederic (2012)
We present a general construction of asymmetric quantum codes based on additive codes under the trace Hermitian inner product. Various families of additive codes over F4 are used in the construction of many asymmetric quantum codes over F4.